This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Firstly, the curve r ( t ) doesn't pass through the origin, but we can proceed and pretend that t = 0 corresponds to the origin point, since that's what the correct answer assumes. In reality the arc-length calculated is between the point (0,1,1) and the second one given. Also notice that the second point given corresponds to t = 1 . We know that the arc-length of a parametric curve is given by
L = ∫ a b ∣ r ′ ( t ) ∣ d t = ∫ a b ( d t d x ) 2 + ( d t d y ) 2 + ( d t d z ) 2 d t
where r ′ ( t ) = ⟨ 2 , e t , − e − t ⟩ . Plugging this into the above equation with a = t 1 = 0 and b = t 2 = 1 gives
L = ∫ 0 1 e 2 t + 2 + e 2 t 1 d t
and notice that e 2 t + 2 + e 2 t 1 = ( e t + e t 1 ) 2 to give
L = ∫ 0 1 ( e t + e t 1 ) 2 d t = ∫ 0 1 e t + e t 1 d t = e t ∣ ∣ 0 1 − e − t ∣ ∣ 0 1 = e − e 1